2007
DOI: 10.1002/ijc.22720
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effects of celecoxib with 5‐fluorouracil depend on IFN‐γ

Abstract: Cyclooxygenase-2 (COX-2) inhibitors are effective chemopreventive agents against colorectal cancers. For treatment of advanced cancers, combination of COX-2 inhibitors and chemotherapy has been attempted, but the results are still controversial. In the present study, the effects of the COX-2 inhibitor celecoxib on the anticancer potential of chemotherapy, and its mechanisms of action were investigated in point of the angiogenesis, using an advanced cancer model in mice. BALB/c mice were inoculated with colon 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
(22 reference statements)
3
25
0
Order By: Relevance
“…In addition, drugs are combined having different effects, and each drug can be used at its optimal dose, without intolerable side effects (34). Currently, growing evidence suggests that the anticancer activity of standard chemotherapeutic agents can be enhanced by using CXB (35). For instance, Zhang et al showed that the combination of low concentrations of sorafenib (SOR) and CXB in A549 tumor cells significantly suppressed the proliferation in vitro and suppressed tumor growth in vivo compared to the actions of either agent alone (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, drugs are combined having different effects, and each drug can be used at its optimal dose, without intolerable side effects (34). Currently, growing evidence suggests that the anticancer activity of standard chemotherapeutic agents can be enhanced by using CXB (35). For instance, Zhang et al showed that the combination of low concentrations of sorafenib (SOR) and CXB in A549 tumor cells significantly suppressed the proliferation in vitro and suppressed tumor growth in vivo compared to the actions of either agent alone (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although the suppression of angiogenesis that occurs with NSAID treatment alone may not be sufficient to inhibit tumour growth, NSAIDs may enhance the antiangiogenic and antiproliferative effects of certain antitumour drugs (123,125,127). As shown by Irie et al (125), celecoxib alone did not significantly inhibit tumour growth, although it did exhibit a certain antiangiogenic activity. However, in combination with 5-FU, celecoxib enhanced the antitumour effect of 5-FU and significantly suppressed angiogenesis and tumour growth, likely via the inhibition of VEGF and the induction of IFN-γ (125).…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Vivomentioning
confidence: 93%
“…Certain studies demonstrated the ability of NSAIDs, particularly selective COX-2 inhibitors, to suppress tumour growth by inhibiting angiogenesis and cell proliferation (131,132). Although the suppression of angiogenesis that occurs with NSAID treatment alone may not be sufficient to inhibit tumour growth, NSAIDs may enhance the antiangiogenic and antiproliferative effects of certain antitumour drugs (123,125,127). As shown by Irie et al (125), celecoxib alone did not significantly inhibit tumour growth, although it did exhibit a certain antiangiogenic activity.…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Vivomentioning
confidence: 99%
“…Administration of sulindac or celecoxib to mice with gastric cancer xenografts decreased levels of both FGF and VEGF, effectively reducing microvessel density within the tumor [76]. Celecoxib in conjunction with chemotherapy reduced VEGF in mice implanted with a colon cancer cell line and also increased IFN-gamma, which is important for antitumor immunity [77]. Zhou et al reported that post-operative gastric cancer patients given celecoxib had reduced VEGF levels in cancerous tissue compared to those that received surgical intervention alone [78].…”
Section: Cox-2/pge 2 Promotes Angiogenesis and Metastasismentioning
confidence: 99%